Analysis of Food Security of Rubber Farmers in Lubuk Raja District, Ogan Komering Ulu Regency - Amel Permatasari; Munajat Munajat; Yetty Oktarina (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the level of household food security among rubber farmers in Lubuk Raja District, Ogan Komering Ulu Regency, using the proportion of food expenditure as an indicator of food security. Methodology/Approach: A survey method was employed in January 2024. The population consisted of 300 rubber farmers owning approximately 1 hectare of land. Using the Slovin formula with a 10% margin of error, 70 respondents were selected through simple random sampling. Results: The findings show that the average monthly food expenditure of rubber farmer households was IDR. 1,328,204, while non-food expenditure averaged IDR. 1,434,749, resulting in a total household expenditure of IDR. 2,762,953 per month. The proportion of food expenditure reached 48.07%, which is below the 60% threshold commonly used to indicate food security. Conclusions: Rubber farmer households in Lubuk Raja District can be classified as food secure, as reflected by their relatively low proportion of food expenditure. Despite fluctuations in rubber prices, the structure of household income and expenditure indicates adequate access to food. Limitations: his study is limited to the use of food expenditure proportion as the sole indicator of food security and focuses only on rubber farmers with 1-hectare land ownership in a single district. Contributions: This research contributes empirical evidence on household food security conditions among rubber farmers in rural Indonesia and provides useful insights for policymakers in designing targeted agricultural and food security programs, particularly in regions highly dependent on plantation commodities.